2010
DOI: 10.15282/ijame.2.2010.3.0011
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Mixed Convective Heat Transfer using Lattice Boltzmann Method

Abstract: In this paper, mixed (forced-natural) convective heat transfer around a heated square cylinder located inside a lid driven cavity has been studied numerically using the lattice Boltzmann method in the range of 100≤ Re ≤ 1000 with the corresponding Richardson number 0.01≤Ri≤10. The double-population lattice Boltzmann formulation is used as the governing equation. Two dimensional nine-velocity models are used for the computation of the velocity field while a four-velocity model is used for the computation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The flow inside a square cavity has been widely used to demonstrate fluid flow using simple geometry. The flow structure in a one-sided lid-driven cavity problem has been reported by many researchers (Ghia, Ghia, & Shin, 1982;Idris, Ammar, Tuan Ya, & Amin, 2013;Idris, Irwan, & Ammar, 2012;Musa, Abdullah, Azwadi, & Zulkifli, 2011;Rosdzimin, Zuhairi, & Azwadi, 2010;Sidik & Attarzadeh, 2011). Later, research on different cavity geometries has been reported, such as a deep cavity (Patil, Lakshmisha, & Rogg, 2006), semi-circular cavity (Yang, Shi, Guo, & Sai, 2012), trapezoidal cavity (Zhang, Shi, & Chai, 2010) and triangular cavity (González, Ahmed, Kühnen, Kuhlmann, & Theofilis, 2011).…”
Section: Introductionmentioning
confidence: 81%
“…The flow inside a square cavity has been widely used to demonstrate fluid flow using simple geometry. The flow structure in a one-sided lid-driven cavity problem has been reported by many researchers (Ghia, Ghia, & Shin, 1982;Idris, Ammar, Tuan Ya, & Amin, 2013;Idris, Irwan, & Ammar, 2012;Musa, Abdullah, Azwadi, & Zulkifli, 2011;Rosdzimin, Zuhairi, & Azwadi, 2010;Sidik & Attarzadeh, 2011). Later, research on different cavity geometries has been reported, such as a deep cavity (Patil, Lakshmisha, & Rogg, 2006), semi-circular cavity (Yang, Shi, Guo, & Sai, 2012), trapezoidal cavity (Zhang, Shi, & Chai, 2010) and triangular cavity (González, Ahmed, Kühnen, Kuhlmann, & Theofilis, 2011).…”
Section: Introductionmentioning
confidence: 81%
“…Fluid behaviour and thermal field in lid-driven trapezoidal cavities is a topic of great importance to many researchers due to its significance in practical engineering applications. These applications include solar energy, power stations, heat exchanger devices, nuclear reactors, the technology of lubrication, combustion of atomized liquid fuels and cooling of electronic equipment [1,2]. The forced convection process is achieved when the fluid motion is caused by using external devices such as a compressor, fan, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The mixed convection heat transfer in a lid-driven cavity with different geometries and thermal boundary conditions was studied by many authors . The cavity with lid-driven is considered in different shapes, such as square [1][2][3][4][5][6][7][8], trapezoidal (or triangle) [9][10][11][12][13], rectangle [14][15][16][17][18], and other geometries [19][20][21][22][23][24] with various thermal and hydrodynamic boundary conditions. Tables 1-4 present a summary of these works.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental Re D range is 50-4000, and in the second part, similar results are developed based on numerical simulations for Pr = 0.72 and 40 ≤ Re D ≤ 200. The experimental and numerical results for optimal spacing and maximum thermal conductance are explained and correlated analytically by intersecting the small-and large-spacing asymptotes of the thermal conductance function (Stanescu, Fowler, & Bejan, 1996;Rosdzimin, Zuhairi, & Azwadi, 2010). A calculation procedure for two-dimensional elliptic flow is applied to predict the pressure drop and the heat transfer characteristics of laminar and turbulent flow of air across the tube banks.…”
Section: Introductionmentioning
confidence: 99%